Glossodiversité : Quand ? Comment ? Pourquoi ? - Gilbert Dalgalian (Lengas)
This article explores the concept of glossodiversity by examining the relationship between linguistic diversity and biodiversity, while challenging the reductive view that links languages to identities. The author highlights the importance of languages in the construction of individual identity and warns against the risks of their loss. Furthermore, the article calls for an awareness of the crucial role of glossodiversity in fostering creativity, adaptability, and collective survival. It emphasizes the importance of minority languages and language policies in this context. Ultimately, the article advocates for the preservation and promotion of diversity in all its forms to build a supportive and responsible future.